Cyclometalation Reactions Five-Membered Ring Products as Universal Reagents - Omae, Iwao.; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2014)
This book provides a review of cyclometalation reactions and organometallic intramolecular-coordination five-membered ring products, the most active type of reactions in synthetic organic reactions and their products. Included is the discovery of intramolecular-coordination bonds in cyclometalation reactions and the characteristics of those reactions, as well as the reasons that their five-membered ring compounds are very easily synthesized through such reactions. In addition, the applications of cyclometalation reactions and five-membered ring products, synthetic applications, catalysts, and other products are described. These topics are of special interest for industrial researchers.
From the Contents: Discovery of Intramolecular-Coordination Bonds in Cyclometalation Reactions with Main Group Metal Compounds -- Verification of the Formation of Intramolecular-Coordination Bonds in Cyclometalation Reactions with Transition Metal Compounds -- Organometallic Intramolecular-Coordination Compounds -- Characteristics of Cyclometalation Reactions for Organometallic Intramolecular-Coordination Five-Membered Ring Compounds -- Reasons That Organometallic Intramolecular-Coordination Five-Membered Ring Compounds Are Very Easily Synthesized Through Cyclometalation Reactions -- Applications.
Keywords: Chemistry; Chemistry, Organic; Catalysis; Chemistry; Organometallic Chemistry; Catalysis